2018
DOI: 10.1097/mpa.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survivors of Pancreatic Cancer

Abstract: Objectives Pancreatic cancer continues to carry a poor prognosis with survival rates that have had minimal improvement over the past four decades. We report a population-based, comprehensive analysis of long-term survivors of pancreatic adenocarcinoma diagnosed in the diverse population of California. Methods Data from the California Cancer Registry were used to evaluate long-term survival. A total of 70,442 patients diagnosed with pancreatic adenocarcinoma between 1988 and 2009 were identified. Logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…Univariate and multivariate analyses demonstrated that high USP5 expression is an independent risk factor for pancreatic cancer. Our results also showed that differentiation is an unfavorable independent risk factor for pancreatic cancer, which have been proved by previous study 25 . In short, patients with high USP5 expression tend to have a poor prognosis, which is consistent with publicly databases.…”
Section: Discussionsupporting
confidence: 90%
“…Univariate and multivariate analyses demonstrated that high USP5 expression is an independent risk factor for pancreatic cancer. Our results also showed that differentiation is an unfavorable independent risk factor for pancreatic cancer, which have been proved by previous study 25 . In short, patients with high USP5 expression tend to have a poor prognosis, which is consistent with publicly databases.…”
Section: Discussionsupporting
confidence: 90%
“…Most patients with PDAC remain asymptomatic until the disease develops to an advanced inoperable stage, leading to its disappointing prognosis [4].The determination of prognostic factors in patients with PDAC is essential for predicting the outcome and for identifying appropriate treatment strategies. Known clinical prognostic parameters include age, tumor stage, lymph node status, grading, perineural invasion, and for resected patients' resection status, adjuvant chemotherapy and hospital volume [5][6][7].Moreover, it has long been recognized that the tumor microenvironment and an involvement of the immune system play a distinctive role in the biological behavior of cancer [8]. PDACs are characterized by an immunosuppressive microenvironment due to the dysfunction of the immune system, which is a result of the involvement of multiple types of immune cells, including cancer-associated fibroblasts, regulatory T cells, myeloid-derived suppressor cells, tumor-associated macrophages, and tumor-infiltrating lymphocytes [9].…”
mentioning
confidence: 99%
“…The determination of prognostic factors in patients with PDAC is essential for predicting the outcome and for identifying appropriate treatment strategies. Known clinical prognostic parameters include age, tumor stage, lymph node status, grading, perineural invasion, and for resected patients' resection status, adjuvant chemotherapy and hospital volume [5][6][7].…”
mentioning
confidence: 99%
“…CS was defined as the probability of surviving an additional number of 'y' years, given that a patient had already survived for 'x' years, and was calculated as CS (x|y) = S (x?y) /S (x) , with S (x) representing the overall survival at x years estimated using the Kaplan-Meier method. 12 For example, to estimate the CS for surviving 2 more years for patients who had already have survived 3 years after surgery, CS (3|2) is calculated by dividing the 5-year Kaplan-Meier survival estimate S (5) by the 3-year Kaplan-Meier survival estimate S (3) . 8,[19][20][21] Median CS was also determined at specific times and was derived from Kaplan-Meier estimates by discarding the patients who died before that time.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Approximately 16% of all patients will undergo surgical resection, with a 5-year survival rate of 15-20%. [3][4][5] Survival following resection of pancreatic cancer has improved because of better adjuvant treatment strategies. 6,7 Therefore, increasing numbers of patients with pancreatic cancer will survive the first year following surgery and these patients might want to be informed about accurate data on survival estimates during follow-up.…”
mentioning
confidence: 99%